PENINGKATAN HASIL BELAJAR AKIDAH AKHLAK MELALUI METODE JIGSAW SISWA MTSN 1 SAROLANGUN - Yusria; Alya Khairunnisa; Amiratus Soliha; Muhammad Fajar Mauliddin An-Nabawi; Mujibur Rahman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study discusses the application of the Jigsaw learning method to improve student learning outcomes in the Aqidah Akhlak subject at Mtsn 1 Sarolangun, this research is classroom action research (PTK). Data collection uses the methods of observation, interviews, test questions and documentation. The observation method is used to measure teacher and student activities each cycle. The interview method was used to find out opinions and descriptions of learning at Mtsn 1 Sarolangun, the test method was used to determine students' learning abilities after taking part in learning using the Jigsaw method, and documentation was used to get an idea of ​​what happened in the classroom while learning was taking place. The results of this research show that the use of the jigsaw method was able to improve the learning outcomes of class VII Mtsn 1 Sarolangun students, namely in the first cycle the average student score was 70% and increased in the second cycle to 90%. Based on the results of the data analysis obtained, it can be concluded that learning Aqidah Akhlak using the Jigsaw method can improve student learning outcomes.